EVALUATING PERFORMANCE IN RESIDENTIAL COMPLEX PROJECT - KASHKOOL, AFRAH M. H. (Journal of Duhok University, 2023)
Performance is an essential factor in construction projects, residential complex building projects are widely constructed recently in Iraq. The research objective is to identify and evaluate key performance indicators (KPIs)  relevant to assessing these projects' success.the key performance indicators (KPIs) were specified according to the literature and the expert’s opinions. a questionnaire was distributed to extract the most important KPIs and factors. The questionnaire was carefully designed to ensure accuracy. KPIs were specified using the Relative Importance Index (RII ) The research investigated and identified the top ten factors influencing performance in construction projects. The findings revealed that the availability of highly qualified and experienced personnel ranked first, followed by the importance of reviewing failures and resolving them. The cost of materials and equipment, the organization’s quality assessment system, and the coordination of information between the owner and project parties were also identified as significant factors. Additionally, the quality of equipment and raw materials, planned time to build the project, compliance with specifications, training human resources on project-specific skills, and the application of health and safety factors in the organization were recognized as crucial considerations. the work sequence according to schedule and the availability of resources as planned during the project duration have an impact on project performance. These findings contribute to understanding the key factors that influence successful outcomes in construction projects.